Genomic Characterization of Extensively Drug-Resistant NDM-Producing Acinetobacter baumannii Clinical Isolates With the Emergence of Novel blaADC-257 - Zafer, Mai M.; Hussein, Amira F. A.; Al-Agamy, Mohamed H.; Radwan, Hesham H.; Hamed, Samira M. (Frontiers in Microbiology, 2021)
Acinetobacter baumannii has become a major challenge to clinicians worldwide due to its high epidemic potential and acquisition of antimicrobial resistance. This work aimed at investigating antimicrobial resistance determinants and their context in four extensively drug resistant NDM-producing A. baumannii clinical isolates collected between July and October 2020 from Kasr Al-Ainy Hospital, Cairo, Egypt. A total of 20 A. baumannii were collected and screened for acquired carbapenemases (blaNDM, blaVIM and blaIMP) using PCR. Four NDM-producer A. baumannii isolates were identified and selected for whole genome sequencing, in silico multilocus sequence typing, and resistome analysis. Antimicrobial susceptibility profiles were determined using disk diffusion and broth microdilution tests. All blaNDM-positive A. baumannii isolates were extensively drug resistant (XDR). Three isolates belonged to high-risk international clones (IC), namely IC2 corresponding to ST570Pas/1701Oxf (M20) and IC9 corresponding to ST85Pas/ST1089Oxf (M02 and M11). For the first time, we report blaNDM-1 gene on the chromosome of an A. baumannii strain that belongs to sequence type ST164Pas/ST1418Oxf. Together with AphA6, blaNDM was bracketed by two copies of ISAba14 in ST85Pas isolates possibly facilitating co-transfer of amikacin and carbapenem resistance. A novel blaADC allele (blaADC-257) with an upstream ISAba1 element was identified in M19 (ST/CC164Pas and ST1418Oxf/CC234Oxf). blaADC genes harbored by M02 and M11 were uniquely interrupted by IS1008. Tn2006-associated blaOXA-23 was carried by M20. blaOXA-94 genes were preceded by ISAba1 element in M02 and M11. AbGRI3 was carried by M20 hosting the resistance genes aph(3`)-Ia, aac(6`)-Ib`, catB8, ant(3``)-Ia, sul1, armA, msr(E), and mph(E). Non-synonymous mutations were identified in the quinolone resistance determining regions (gyrA and parC) of all isolates. Resistance to colistin in M19 was accompanied by missense mutations in lpxACD and pmrABC genes. The current study provided an insight into the genomic background of XDR phenotype in A. baumannii recovered from patients in Egypt. WGS revealed strong association between resistance genes and diverse mobile genetic elements with novel insertion sites and genetic organizations.